The essential yeast RNA binding protein Npl3p is methylated - Siebel, Christian W. (The National Academy of Sciences of the USA, 1996)
Arginine methylation is a prevalent modification found in many RNA binding proteins, yet little is known about its functional consequences. Using a monoclonal antibody, 1E4, we have shown that the yeast NPL3 gene product Npl3p, an essential RNA binding protein with repeated RGG motifs, is arginine-methylated in vivo. The 1E4 epitope can be generated by incubating recombinant Npl3p with partially purified bovine arginine methyltransferase, and peptides that specifically inhibit arginine methyltransferases block this reaction. Npl3p methylation requires S-adenosyl-l-methionine and also occurs in yeast extracts. An Npl3p deletion mutant lacking the RGG domain is not a substrate for methylation, suggesting that the methylation sites lie within the RGG motifs. The discovery of arginine methylation in a genetically tractable organism provides a powerful entrée to understanding the function of this modification, particularly in view of the many roles postulated for Npl3p in RNA processing and transport. The recent discovery of phosphorylated serine residues within the RGG domain suggests a hypothesis in which a molecular switch governed by methylation and phosphorylation regulates the biochemical properties of the Npl3p RGG domain.